2008
DOI: 10.1177/1938640007312300.
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Lisfranc Ligament

Abstract: Most authors agree that anatomic reduction is the key to optimal results in treatment of injuries of the Lisfranc joint; a few controversies remain. One controversy is the identification of the strongest ligament of the second metatarsal-medial cuneiform articulation-the critical ligament of the Lisfranc joint. The purpose of this study is to objectively quantify the cross-sectional area of each ligament of this crucial joint. Twenty cadaveric feet were dissected to isolate the second metatarsal-medial cuneifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 16 publications
0
35
3
1
Order By: Relevance
“…[12], and 7.68 ± 1.25 mm [15]. For the plantar ligament, the bundle thickness was 3.25 ± 0.97 mm [15]. Therefore, no consensus has been obtained, and there are differences from the results of the present study.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…[12], and 7.68 ± 1.25 mm [15]. For the plantar ligament, the bundle thickness was 3.25 ± 0.97 mm [15]. Therefore, no consensus has been obtained, and there are differences from the results of the present study.…”
Section: Discussioncontrasting
confidence: 87%
“…In previous studies of the Lisfranc ligament, it was reported that the fiber bundle length was 8.02 ± 1.5 mm [12], 9.17 ± 1.5 mm (6.6-10.95) [13], and 33.7 ± 0.8 mm (2. [12], and 7.68 ± 1.25 mm [15]. For the plantar ligament, the bundle thickness was 3.25 ± 0.97 mm [15].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18][19] The dorsal ligaments are the weakest in the complex and are the first to fail in the typical indirect injury mechanism associated with subtle Lisfranc injuries. [11][12][13][14][15][16][17][18][19] The dorsal ligaments are the weakest in the complex and are the first to fail in the typical indirect injury mechanism associated with subtle Lisfranc injuries.…”
Section: Anatomy and Biomechanicsmentioning
confidence: 99%
“…Abb. 12) zwischen Os cuneiforme mediale (Cm) und MT II besonders stabilisiert [25] [26]. Die Diagnostik schwerer Luxationsfrakturen stellt röntgenologisch keine besondere Herausforderung dar.…”
Section: Verletzungen Des Lisfranc-gelenksunclassified